Pediatric Tacrolimus-Induced Reversible Cerebral Vasoconstriction Syndrome after Heart Transplantation - Shabo, Leah; Ishaque, Mariam; Sarathy, Danyas; Kumar, Jeyan; Xixis, Kathryn; Park, Min (Journal of Pediatric Neurology, 2022)
Reversible cerebral vasoconstriction syndrome (RCVS) is a rare post-organ transplantation complication. While uncommon, complications of post-transplant RCVS can be devastating, with sequelae including ischemic or hemorrhagic stroke and potential significant neurological morbidity. There is a paucity of literature on tacrolimus-mediated RCVS, particularly in the pediatric population. To date, only five case reports have been published, with the youngest patient being 15 years of age. We report the youngest case to date of post-heart transplant tacrolimus-induced RCVS in a 6-year-old male. The present case highlights the necessity of urgent imaging in suspected cases of RCVS, the potential diagnostic challenges surrounding the etiology of headache, the benefits of treating underlying cerebral vasospasm, and the importance of rapid discontinuation of the offending agent for the remission of symptoms and prevention of long-term sequelae.
Keywords: reversible cerebral vasoconstriction syndrome; post-heart transplant; tacrolimus